Nebulizer Operational Time Control Based on Drug Volume and Droplet Size Using Fuzzy Sugeno Method - Ibnu Rizal Fadhlurahman Arif; Ahmad Firdausi; Galang P. N. Hakim (Journal of Robotics and Control (JRC), 2021)
Nebulizer is one of the electro medic devices that serve to provide therapy for patients who experience abnormalities or disorders of the respiratory tract. Nebulizer system works using piezo electronic device to produces high frequency vibration. With this high frequency vibration the drug liquid molecules breaks down become fumes, thus it can easily to inhale for patient even for children. Unfortunately like other aerosol drug delivery system, the operation of nebulizer is also still manual. The patient doesn’t really know when the drug is empty on the canister. The nurses also need to check in regularly to see if the drugs are empty or not. In this paper a fuzzy sugeno methods is used to give prediction of nebulizer time operational. We propose fuzzy sugeno to calculate the time operational nebulizer using two parameters, such as drug droplet size and drug liquid volumes that have been administer by nurses. Using fuzzy sugeno method we can solve the nebulizer manual operational time problem. Our result show that the longest operational time was 26.07 minutes, this achieve when liquid volume was 5 ml and the size of drug droplet was 1 um. Meanwhile for the shortest operational time was 8.07 minutes, this achieve when liquid volume was 10 ml and the size of drug droplet was 4 um. We can conclude that we had successful to control nebulizer operational time using fuzzy sugeno method.